Hypergraph models of hydrocarbon molecules and their applications in computer chemistry - M. I. Skvortsova; I. I. Fashutdinova; N. A. Mikhailova (Тонкие химические технологии, 2014)
A new form of representing the structures of saturated hydrocarbons as hypergraphs of special kind is suggested. A vertex of such hypergraph corresponds to a carbon atom in the molecule, and a hyperedge is defined as a set of vertices corresponding to some fixed carbon atom and all carbon atoms bounded with it. The comparison of the traditional graph model and the suggested hypergraph model using definite quantitative criteria related to some tasks of computer chemistry is fulfilled. For these investigations some set of hydrocarbons presented by their structural formulae is used. In particular, different invariants and codes of graphs and hypergraphs were calculated and their degeneration on the given set of structures was studied and compared. Two models were also compared by the ability of some local vertex invariants derived from them to distinguish topologically nonequivalent vertices in the traditional graph model. It is shown that in all cases in accordance with the used criteria the hypergraph model is better than the graph model. Besides, a number of structure–property relationships on the base of invariants of the suggested hypergraphs was obtained